Piracy as Labour Struggle - Gavin Mueller (tripleC: Communication, Capitalism & Critique)
This paper examines the organization of digital piracy in the context of reshaping labor under neoliberalism. It discusses the practices by which enclosures of intellectual property are resisted by drawing from literature on the labor process, and examining the historical emergence of piratical practice on electronic bulletin board systems. These pirates sought, above all, to preserve autonomous, self-managed working conditions in the face of tendencies to commodify, enclose, and deskill.